Religiusitas, Identitas Keagamaan, dan Moderasi Beragama Mahasiswa PTKI: Studi Kasus di IAIN Kediri - Yusuf, Moh. Asror; Winastuti, Novi Wahyu (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to explain the relationship between religiosity and religious moderation, as well as the dynamics of students’ religious identity at PTKI in Kediri. The research employed a mixed-method approach using a sequential explanatory strategy. The study was conducted at the State Islamic Institute (IAIN) of Kediri, involving seventh-semester students of the Islamic Psychology Department, Faculty of Ushuluddin and Dakwah. The findings reveal that religiosity has a significant influence on religious moderation—students with higher religiosity exhibit stronger moderation. Religious understanding and spiritual experience play a major role in shaping a moderate attitude. The respondents’ religious identities vary: achievement (47.9%), moratorium (16%), foreclosure (10.6%), and diffusion (25.5%). The achievement identity represents the most mature condition, characterized by commitment following a process of exploration, formed through knowledge, parental influence, and peer interactions. These findings emphasize the importance of strengthening moderate religious understanding and fostering supportive social environments to enhance students’ attitudes of religious moderation.